Smells Like Anthelmintic Resistance—Gastrointestinal Prevalence, Burden and Diversity in Dogs from Portugal - Batista, Cláudia Luís (2024)
Funding: The participation of Teresa Letra Mateus was funded by national funds through FCT-Fundacao para a Ciencia e Tecnologia, I.P., with the scope of the project UIDB/05937/2020 with DOI identifier https://doi.org/10.54499/UIDB/05937/2020 and UIDP/05937/2020 with DOI identifier https://doi.org/10.54499/UIDP/05937/2020. The participation of Maria Aires Pereira was supported by the projects GHTM-UID/04413/2020 and LA-REAL-LA/P/0117/2020, and CERNAS UIDB/00681/2020, funded by the Portuguese Foundation for Science and Technology (FCT). The participation of Claudio Araujo-Paredes was funded by national funds through FCT-Fundacao para a Ciencia e a Tecnologia, I.P., within the scope of project UIDB/05975/2020.